LA CULTURA PANÓPTICA Y LOS GÉNEROS NEOTELEVISIVOS - Sanabria, Carolina (Universidad de Costa Rica, 2013)
This article is based on the premise that technologic development that society has reached today allows it to extend the panoptic tendency -initially architectonic and later photographic- to two TV genders: The hidden camera and mainly the reality show (if we use Big Brother as a paradigm). From this moment, we can point out that the surveillance underlying this visual articulation ends up extrapolating to the spectacular structure.